Developing speaking material in English program at Madrasah Ibtidaiyah Nurul Ummah Kotagede - Muhammad Sidiq Satriayudha (Journal of English Language and Pedagogy, 2021)
This research was aimed to develop an English-Speaking Material for English program at Madrasah Ibtidaiyah Nurul Ummah and to figure out the efficacy of the developed product. This research was conducted in response to the problems faced by the teacher in developing students’ speaking skills, especially in elementary school. This is an R&D research which adopted from Borg and Gall's (1982) Model in the R&D method. The procedures of this research comprise 1) Research and Information Collecting, 2) Planning and Drafting, 3) Draft revision, 4) Field Testing, 5) Revision and 6) Final Product. The data were collected from observation and teacher’s interviews. The first stage is research and Information Collecting. The result of the first stage is about students’ need analysis. The content of need analysis are necessities, want, lack. The target situation of the English Active Program is the students can master speaking English in daily life’s context. Then, the first problems or lacks of the students in learning speaking are about vocabulary and pronunciation. Based on the result the researcher has developed the course grid and the speaking material. The result of this product development was beneficial, useful, and appropriate to be used for developing the speaking skills of students of Elementary school. The efficacy of the developed English-speaking materials involves the strengths and weaknesses of the product. The strengths of the developed English-speaking material are the use of the Direct Method and Communicative Language Teaching, the contents of speaking material are based on students ‘daily topics that make students motivated to learn, varied activities in the material stimulate the students speaking activity. This material consists activity that is joyful like a sing a song, games, and group practice. The other side, the weakness of the developed product related to speaking skill are it lacks grammar material.